(untitled) (Conferencea, 2023)
The formation of a new digital culture is accompanied by significant changes in cultural and anthropological practices themselves, where the digital layer is layered and penetrates as another dimension of activity and communication. The new digital environment determines the values and mental attitudes of a person, forms a new one.